Colonoscopy surveillance of colorectal cancer post-surgery in Sanglah General Hospital, Bali, Indonesia: a descriptive study - Gede Eka Rusdi Antara (DiscoverSys Inc., 2021)
Background: The postoperative surveillance of patients treated for colorectal cancer is intended to prolong survival by diagnosing recurrent and metachronous cancers at a curable stage as well as preventing metachronous cancer by detection and removal of precancerous polyps. This study evaluates the surveillance colonoscopy and its association with sociodemographic and clinical findings in a descriptive study.Methods: This is a cross sectional study of colorectal cancer patients who underwent surveillance colonoscopy as follow up after tumor resection from January 2020 to September 2021 in Sanglah General Hospital. Clinical data were gathered from medical records and databases by a qualified reviewer. Data were analyzed descriptively using SPSS version 20 for Windows.Results: The majority of patients who underwent surveillance colonoscopy were male (82.40%), tumor location at rectum (58.8%), stage IV (29.40%), underwent low anterior resection surgery (35.30%) and received Folfox (35.30%) or Capeox (35.30%) adjuvant chemotherapy. There was 2 (11.80%) residual mass found in this study. There was no significant difference between subjects who underwent surveillance colonoscopy with residual mass and without residual mass in all variables assessed (p>0.05).Conclusion: Colonoscopy surveillance plays an important role in early detection for any recurrence or pre-cancer lesion and metachronous cancer in a patient with colorectal malignancies in Sanglah General Hospital, Bali, Indonesia.